Reflexive Methods of Knowledge in Educational Activities: Phenomenological Hermeneutics - T. N. Korneenko (Russian State Vocational Pedagogical University, 2019)
Introduction. Knowledge is one of the most important human needs. Today, lifelong learning and self-education individual skills are of paramount importance for each representative of the society in relation to the world trends of a post-industrial era: economic domination in the innovative sector, progressive increase of intensity of information flows and rates of distribution of high technologies, rapid development of science and industry of knowledge, quickly changing and becoming tougher requirements to professionalism, qualification and creativity of experts irrespective of the sphere of employment. It is obvious that structural formation and improvement of ways of students' thinking is one of the most important tasks of the educational system; reflection is of particular importance. However, the results of training are still defined by the level of development of easily measured operational skills and cognitive qualities (memory, attention, logic), in which the reflection is presented only partially. Reflexive abilities as the mechanism and instrument of knowledge, which assist a personality to understand himself or herself, to comprehend own feelings, actions, acts and complex external realities, in most cases remain unaccounted in educational process and when analysing and evaluating the results.The aim of the article was to justify the need to form reflexive skills of knowledge in students through a combination of phenomenological and hermeneutical methods in daily pedagogical practice.Methodology and research methods. The work is based on the ideas of anthropological and phenomenological approaches in human education and - above all - the philosophic idea of "human-sizedness", which implies anthropological view on a student. The methods of system-based and comparative analysis, as well as the methods of interpretation, synthesis and modelling were used in the course of the research.Results and scientific novelty. The author designates classical linear and neoclassical types of informative models with corresponding to them essentially different explanatory-illustrative and actively-searchable methods, which are used by teachers during classes. The advantages of phenomenological pedagogics are proved: its central category is presented by the phenomenon - sense of any phenomena or processes, which leads to the enrichment of personal experience. In phenomenological approach, the student is regarded as a live, constantly changing character of own personal formation and development; knowledge process is considered as the sequence of acts of understanding and its judgment in close teacher-student interaction. The accumulation of knowledge experience and students'' acquisition of axiological orientations are promoted by the reflexive processes, structuring knowledge conducive to the elaboration of individual strategy and tactics of behaviour. The educational practices, based on the ways of complete development of reflexive informative abilities of individuals in the context of their activity, are known as the anthropopractices, which subject is "human" in the person and the result is self-determination.The characteristics of two leading methods of knowledge - phenomenological and hermeneutical are compared, their similarity and distinction are shown, and possible options of application are shown. The author concludes that integrated usage of phenomenological approach with hermeneutics elements in the educational activity is considered useful.Practical significance. The means of phenomenological hermeneutics described in the article become especially relevant in the conditions of digitalisation and computerisation of pedagogical communication: their use better compensates for the costs of technical methods of training by the means of real teacher-student collaboration through dialogue, knowledge process, experience, interpretation and reflection of the discipline under study.